ActivitÃ© Acaricide Des Huiles Essentielles Du Mentha Pulegium, Origanum Compactum Et Thymus Capitatus Sur Lâ€™acarien Phytophage Tetranychus Urticae Koch (Acari : Tetranychidae) - Aissaoui, Asmae Bakkali; Amrani, Amal El; Zantar, Said; Toukour, Larbi (European Scientific Journal, ESJ, 2018)
The use of botanical acaricides extracted from plants as an alternative to replace the chemical acaricides is an interesting and efficient option to control pests and ameliorate their toxic effects to humans and the environment. The aim of this work was to evaluate the contact toxicity of Pennyroyal mint (Mentha pulegium), oregano (Origanum compactum) and thyme (Thymus capitatus) essential oils against adults, larvae and eggs of two-spotted spider mite Tetranychus urticae Koch (Tetranychidae). The chemical composition of these three plant essential oils was also characterized. Laboratory tests were conducted to determine the acaricidal effect of plant essential oils at several doses in geometric progression. The consequences of treatments on mortality were measured in relationships with concentrations of essential oils. On the other hand, the major constituents of the three essential oils were identified by gas chromatography-mass spectrometer (GC-MS) techniques. GCMS analyses proved that the major compound present in the essential oils of thyme and oregano is carvacrol (55.59 and 55.28% respectively) while the main component of pennyroyal mint essential oil is pulegone (67,63%). Laboratory bioassay results indicated that essential oils of thyme and pennyroyal mint caused the most important acaricidal effects in comparison with the essential oil of oregano. At a concentration of 1%, thyme and pennyroyal eradicate all adults of the mite while oregano causes a mortality of 84.99%. On larvae, the mortality rate of thyme, pennyroyal and oregano is 97.7; 89.47 and 57.89% respectively. The results of the present study concluded that plant essential oils could be useful in promoting research aiming at the development of new agent for pest control from the plants with medicinal values.